THE EFFECT OF INVESTMENT, LABOR, AND EDUCATION LEVEL ON ECONOMIC GROWTH IN INDONESIA IN 2019-2023 - Subagyo, Erlangga Aryaputra; Restikasari, Wenny (Journal of Finance, Economics and Business, 2025)
This research aims to determine the influence of independent variables, namely investment, labor force, and education level, on the dependent variable, economic growth in Indonesia from 2019 to 2023. This study employs a quantitative research approach using secondary data obtained from the Central Statistics Agency (Badan Pusat Statistik). The research method used is Panel Data Regression Analysis. The findings of this study indicate that the variables DDI, labor force, and education level collectively influence economic growth. Additionally, FDI, labor force, and education level collectively influence economic growth. DDI, FDI, labor force, and education level collectively influence economic growth in Indonesia from 2019 to 2023.